2020
DOI: 10.1183/13993003.02718-2020
|View full text |Cite
|
Sign up to set email alerts
|

Progressive fibrosing interstitial lung disease: a clinical cohort (the PROGRESS study)

Abstract: In patients with chronic fibrosing interstitial lung disease (ILD), a progressive fibrosing phenotype (PF-ILD) may develop, but information on the frequency and characteristics of this population outside clinical trials is lacking.We assessed the characteristics and outcomes of patients with PF-ILD other than idiopathic pulmonary fibrosis (IPF) in a real-world, single-centre clinical cohort. The files of all consecutive adult patients with fibrosing ILD (2010–2017) were retrospectively examined for predefined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

24
153
9
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 136 publications
(191 citation statements)
references
References 23 publications
24
153
9
5
Order By: Relevance
“…The percentage of patients with fibrosing ILDs other than IPF that developed progression was estimated at 18–32% in a survey of pulmonary, rheumatology and internal medicine physicians from Japan, the US and four European countries [ 19 ], and at 15% in a US claims database study [ 20 ]. We have previously described a single-centre clinical cohort with PF-ILD as part of the PROGRESS study [ 22 ] where, similarly, 27.2% of patients with a fibrosing ILD other than IPF had a progressive phenotype. In the current study, approximately 47% of patients with fibrosing ILD other than IPF had a progressive phenotype.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The percentage of patients with fibrosing ILDs other than IPF that developed progression was estimated at 18–32% in a survey of pulmonary, rheumatology and internal medicine physicians from Japan, the US and four European countries [ 19 ], and at 15% in a US claims database study [ 20 ]. We have previously described a single-centre clinical cohort with PF-ILD as part of the PROGRESS study [ 22 ] where, similarly, 27.2% of patients with a fibrosing ILD other than IPF had a progressive phenotype. In the current study, approximately 47% of patients with fibrosing ILD other than IPF had a progressive phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, approximately 47% of patients with fibrosing ILD other than IPF had a progressive phenotype. This higher percentage of patients with a progressive phenotype may be due to the fact that patients were tentatively identified based on high consumption of respiratory healthcare in a limited period of time, rather than just the results of sequential PFTs, chest CT and symptoms [ 22 ] or a physician’s survey [ 19 ]. In a preliminary validation study, algorithm 3 was found to have a specificity of 69% and a sensitivity of 46% (data not shown), indicating that our estimates were conservative.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Nasser et al reported the clinical characteristics of patients with PF-ILD other than IPF in a real-world setting. [ 40 ] They reported that 168 of 617 (27.2%) patients with non-IPF, ILD had progressive fibrosing phenotypes. This result was higher than our study; however, the definition of progressive phenotypes used in their study was based on INBUILD trial.…”
Section: Discussionmentioning
confidence: 99%
“…Other non-IPF ILD subtypes that may be associated with a progressive fibrosing phenotype include connective tissue disease-associated ILD (CTD-ILD), idiopathic non-specific interstitial pneumonia (iNSIP), sarcoidosis, hypersensitivity pneumonitis (HP), occupational ILD and unclassifiable ILD (uILD) [ 1 , 2 , 3 , 4 ]. Based on survey data and cohort studies, it is estimated that 30% of non-IPF ILD patients will develop a progressive fibrosing phenotype [ 5 , 6 , 7 ]. In this review, we summarize the current pharmacological management and highlight the unmet needs in patients with non-IPF ILD.…”
Section: Introductionmentioning
confidence: 99%